2020
DOI: 10.1029/2019jd031765
|View full text |Cite
|
Sign up to set email alerts
|

On the Transition From Initial Leader to Stepped Leader in Negative Cloud‐to‐Ground Lightning

Abstract: High‐speed video and electric field change data are used to describe the first 5 ms of a negative cloud‐to‐ground flash. These observations reveal an evolution in character of the luminosity and electric field change pulses as two branches of the leader separately transition from initial leader to propagating as a negative stepped leader (SL). For the first time reported, there is evidence of weak luminosity coincident with the initiating event, a weak bipolar pulse 60 μs prior to the first initial breakdown (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 21 publications
12
21
0
Order By: Relevance
“…The sequence of events leading to IBP#2 fits with the high-speed video and FA data of Stolzenburg et al (2013Stolzenburg et al ( , 2014Stolzenburg et al ( , 2020, which showed that each new classic IBP extended the previous IBP channel. We note that unlike the generation of the first classic IBP, where the large E was caused by hydrodynamics and statistics, the generation of the second classic IBP is caused by the superposition of electric fields due to (1) E of the polarized plasma of IBP#1 and (2) E caused by hydrodynamics and statistics.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 68%
See 3 more Smart Citations
“…The sequence of events leading to IBP#2 fits with the high-speed video and FA data of Stolzenburg et al (2013Stolzenburg et al ( , 2014Stolzenburg et al ( , 2020, which showed that each new classic IBP extended the previous IBP channel. We note that unlike the generation of the first classic IBP, where the large E was caused by hydrodynamics and statistics, the generation of the second classic IBP is caused by the superposition of electric fields due to (1) E of the polarized plasma of IBP#1 and (2) E caused by hydrodynamics and statistics.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 68%
“…In seven CG lightning flashes studied using high-speed video data, Stolzenburg et al (2013) observed a burst of light coincident with each classic IB pulse, and successive bursts developed as "linear segments" that extended for 300-1,500 m. Stolzenburg et al (2013) called the extending linear channel an "initial leader." (Using similar video data, Stolzenburg et al, 2014Stolzenburg et al, , 2020 shown that an initial leader can transition to a stepped leader within 5 ms of flash initiation. This transition takes longer in some flashes.)…”
Section: The First Classic Ib Pulsementioning
confidence: 95%
See 2 more Smart Citations
“…In particular, it is not known what processes lead to the creation of the primary initial leader (PIL) channel and how that channel propagates. In recent years, the use of lightning mapping arrays (Rison et al, 1999;Edens et al, 2012) and VHF radio interferometers (Rhodes et al, 1994;Yoshida et al, 2010;Stock et al, 2014) augmented with fast antennas and optical measurements (Hill et al, 2011;Montanyà et al, 2015;Qi et al, 2016;Tran & Rakov, 2016) have led to the general picture that lightning initiation begins with an ionization event (Stolzenburg et al, 2020), which could be in the form of a powerful narrow bipolar event (Rison et al, 2016) or much weaker VHF source as seen in (e.g. Marshall et al, 2019;Lyu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%